Role of Falcaria vulgaris on Nicotine Toxicity in Rat Hippocampus: Role of Falcaria vulgaris on hippocampus - Roshankhah, Shiva; Arji Rodsari, Babak; Jalili, Cyrus; Salahshoor, Mohammad Reza (Iranian Journal of Pharmaceutical Sciences, 2020)
Falcaria vulgaris (F. vulgaris) is a vegetable that contains antioxidant ingredients. Nicotine is a major risk factor in the development of functional disorder of several organ systems. In this study, 64 male rats were randomly assigned to 8 groups: Sham (saline) group, nicotine group (0.5 mg/kg), F. vulgaris groups (50, 100,and 150 mg/kg), and nicotine + F. vulgaris groups (10, 30, and 60 mg/kg). Treatments were administered intraperitoneally daily for 28 days. FRAP method was applied to determine the total antioxidant capacity. The number of dendritic spines was investigated by Golgi staining technique. Cresyl violet staining method was used to determine the number of neurons in hippocampal region CA1. Also, Griess technique was used to determine serum nitrite oxide level. Nicotine administration increased significantly nitrite oxide level and total antioxidant capacity and a decreased number of neuronal dendritic spines and neurons compared to the sham group (P <0.05). In the F. vulgaris and nicotine + F. vulgaris groups, in all dosages, the number of neurons and neuronal dendritic spines increased significantly while nitrite oxide level and total antioxidant capacity decreased compared to the nicotine group (p < 0.05). It seems that F. vulgaris administration improves hippocampal region CA1 injury in rates because of nicotine.